Rural comunication: evolution x potential - Silva, Nayra Grazielle; Medeiros, Liziany Müller (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The concepts and practices of communication in Brazil are intrinsically linked to the development process of agricultural extension in the country. To develop this paper the methodology adopted was to review the literature procedure, having as base the theory of Freire, Bordenave, Callou, Tauk Santos, Cimadevilla authors, among others, analyzed through articles, books and academic texts, with the aim to discuss the progress and potential of rural communication. With the evolution of communication emerged new actors, new sources and thereby changed the historical notion of extension, which directly involve rural communities, changing their social relations and the ways in which information is disseminated and knowledge isbuilt